I hear what you say, but what are you telling me? the strategic use of nonverbal communication in mediation - Madonik, Barbara G. (Jossey-Bass, 2001)
It has been estimated that less than twenty percent of all human communication is expressed through words. This means that in order to get to the heart of what people are really saying we must have the ability to read the subtext of nonverbal communication. Yet mediators often lack the skills they need to analyze and utilize the rich meaning that is found in nonverbal communication. This step-by-step handbook teaches you how to tune all your senses into what is happening with parties and counsel during mediation and thereby greatly increase your ability to prepare for and facilitate the overall process.